The interactions of bacteriophage Ace and Shiga toxin-producing Escherichia coli during biocontrol - Pinto, Graça (2021)
Strictly lytic phages are considered powerful tools for biocontrol of foodborne pathogens. Safety issues needed to be addressed for the biocontrol of Shiga toxin-producing Escherichia coli (STEC) include: lysogenic conversion, Shiga toxin production through phage induction, and emergence/proliferation of bacteriophage insensitive mutants (BIMs). To address these issues, two new lytic phages, vB EcoS Ace (Ace) and vB EcoM Shy (Shy), were isolated and characterized for life cycle, genome sequence and annotation, pH stability and efficacy at controlling STEC growth. Ace was efficient in controlling host planktonic cells and did not stimulate the production of the Stx prophage or Shiga toxin. A single dose of phage did not lead to the selection of BIMs. However, when reintroduced, BIMs were detected after 24 h of incubation. The gain of resistance was associated with lower virulence, as a subset of BIMs failed to agglutinate with O157-specific antibody and were more sensitive to human serum complement. BIM’s biofilm formation capacity and susceptibility to disinfectants was equal to that of the wild-type strain. Overall, this work demonstrated that phage Ace is a safe biocontrol agent against STEC contamination and that the burden of BIM emergence did not represent a greater risk in environmental persistence and human pathogenicity.